Une discipline en pleine fermentation: Anna Tabaki & Walter Puchner (éds.), First International Conference. Theatre and Theatre Studies in the 21st Century (Athens, 28 September – 1 October 2005). Proceedings - Papalexiou, Elena (Σύγκριση/Comparaison/Comparison, 2012)
[Δεν διατίθεται περίληψη / no abstract available]